Penerapan String Matching Menggunakan Algoritma Boyer-Moore Pada Pengembangan Sistem Pencarian Buku Online - Yusuf Faqih; Yuri Rahmanto; Ahmad Ari Aldino; Budi Waluyo (Forum Kerjasama Pendidikan Tinggi (FKPT), 2022)
The Bayer Moore algorithm can be applied in online book searches with the aim of making it easier for elementary school students to high school students to find books they want to study or find out which subjects are being sought. In developing an online book search using the Bayer Moore algorithm, several stages of research are needed in a planned, regular, and systematic way. This research stage is the development of a research framework that will determine the success of a system. The stages of the Research and Development (R&D) method. The data collection used in this study is a collection of data obtained from crawling results using the PHP programming language. The Crawling data will later become a searchbox about a book that will be able to use Shopee, Tokopedia, and Gramedia links. The systematic procedure used to collect data is quantitative research methods. The implementation of quantitative research methods focuses on the use of numbers, tables, data, codes, rules and to display the results of the data obtained and will be used for data analysis materials on book search websites using the Boyer-Moore algorithm. Based on the results of research and testing results from the book search website using the Boyer-Moore method in php, the results obtained indicate that the program is declared feasible to use, because the associative rules formed and the resulting search value are the same as the output of the developed program.